Near-surface ozone pollution and planting decision: evidence from China crop structure - Liu, Yanbo; Guo, Mingshun (Frontiers in Sustainable Food Systems, 2025)
Crop planting structure fundamentally shapes food security while serving as a critical pathway for high-quality agricultural development. This study examines the relationship between near-surface ozone pollution and cash crop cultivation using panel data from Chinese prefecture-level cities (2014–2019). Through Pedroni cointegration tests and spatial autocorrelation analysis, this study finds that: ozone pollution in China exhibits distinct regional characteristics, with expanding high-concentration zones concentrated in central and southern regions. Cash crop (it refers to crops that provide raw materials for industry, especially light industry) cultivation areas exhibit significant spatial autocorrelation and clustering patterns across Chinese prefecture-level cities. A long-term negative cointegration relationship between ground-level ozone pollution and cash crop planting shares. The impact of ozone concentration on the planting area of cash crops shows an inverted U-shaped pattern. The inflection point is when the near-surface ozone concentration is 64.81 ppb. The vast majority of cities (O3 > 64.81 ppb, N = 1,597) are on the right side of the inflection point, accompanied by a negative spatial spillover effect. This article argues that the government should prioritize the development of ozone-resistant crop varieties and the establishment of farming systems that are adaptable to odor pollution, in order to mitigate its negative impact on agricultural production.